Default in Online Lending: A Legal Review of Standard Clauses and Consumer Protection Against Breach of Contract Claims - Fernando Tantaru; Valentino Dinatra Soplantila (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: This article examines the legal challenges surrounding Default (failure to repay) in online lending agreements dominated by standard clauses. The rapid growth of digital financial services has enabled wider access to credit; however, this convenience is not matched by equitable legal protection for debtors. In practice, delayed repayments are immediately treated as default, without considering whether the agreement itself was substantively fair. Purposes of the Research: The purpose of this study is to analyze the legal standing of debtors who commit galbay in contracts made using standard clauses that tend to favor creditors. This study also aims to evaluate whether such defaults can be directly categorized as breach of contract under Indonesian law, and to explore possible legal reform to enhance consumer protection. Methods of the Research: This research applies normative juridical methods, with a statutory and conceptual approach. The study refers to provisions in the Indonesian Civil Code, Consumer Protection Law, constitute violations of the Electronic Information and Transactions Law, and Financial Services Authority regulations, while also applying theories such as contractual justice, good faith doctrine, and equilibrium contract theory. Data are obtained from legislation, legal doctrine, literature review, and court rulings. Results Main Findings of the Research: The findings show that the debtor’s legal position in online lending is structurally disadvantaged due to unequal bargaining power and the use of exploitative standard clauses. This study argues that Default cannot be directly equated with breach of contract because essential elements of valid default - such as genuine consent and proper notification - are often absent. The novelty of this research lies in its critical framing of online lending default as a structural, rather than individual, failure, thereby requiring a justice-oriented interpretation to prevent systemic exploitation.